Kielikoulusta yliopistoon Kääntäjänkoulutuksen historiaa 1960-luvulta 1980-luvulle - Paloposki, Outi; Jääskeläinen, Riitta (Finland, 2025)
The article examines the history of translator training in Finland. The planning for the new training took place in the early 1960’s and led to the birth of Language Institutes in the towns of Turku and Tampere (1966) and later in Savonlinna (1968) and Kouvola (1971). This new type of language studies was largely based on the need to adapt third level education, both in terms of the mid-sixties demographic changes and of the perceived need for professional education. The institutes first gave two-year courses in one language; soon a third year and another language were added to the training programmes to improve the graduates’ employment prospects. In 1981 Language Institutes became part of the Finnish university system and the institutes were remodelled into degree programmes in Translation and Interpreting. These developments are examined in the light of archived documents, with a view to shedding light onto the educational but also the material environments of translator training.